2013
DOI: 10.1371/journal.pone.0058973
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Intake: Knowledge, Attitudes and Practices in Shandong Province, China, 2011

Abstract: ObjectiveTo investigate the knowledge, attitudes and practices (KAP) for dietary sodium intake among adult residents of Shandong Province, ChinaMethodsIn 2011, we conducted a cross sectional survey among a representative sample of 15,350 adults aged 18 to 69 years using a standardized questionnaire to assess their KAP for sodium. Variation in the KAPs by gender, and residence location were compared using the Chi-square tests. Predictors for the ‘intention to’ and ‘currently taking action to’ reduce sodium inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
60
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 9 publications
14
60
2
1
Order By: Relevance
“…Reading food additional information and nutritional labels are known as core behavior of dietary salt. 10,18 The findings indicated only a limited number of participants always considering packaged indication. About one-fifth for the CHT group and onethird for the UHT group were never paying attention of food indication.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Reading food additional information and nutritional labels are known as core behavior of dietary salt. 10,18 The findings indicated only a limited number of participants always considering packaged indication. About one-fifth for the CHT group and onethird for the UHT group were never paying attention of food indication.…”
Section: Discussionmentioning
confidence: 92%
“…With this consideration, the effort to increase knowledge, attitude and behavior related to dietary salt is strategically important, especially for patients with hypertension. [9][10][11] Increasing hypertension population's knowledge, and improving their attitude and behavior related to salt is crucial, however, understanding on their knowledge and behavior are the first stage of action. To date, there is limited information about knowledge, attitude and behavior related to dietary salt among patients with hypertension in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas a study in China among general population found that almost all of the urban and rural population use low quantity of salt in cooking. 22 But the practice of using low salt/sodium alternatives of the current population is far less than the result of another Indian study (34%). 18 Less processed food consumption is another important practice to reduce the consumption of salt as this type of food contain higher amount of salt.…”
Section: Discussionmentioning
confidence: 84%
“…This practice of lowering salt intake revealed that one third of the population looked at the sodium content on food level which is higher than the rates of other studies. [18][19][20][21][22] Near half of the study population practiced to limit salt intake such as used low quantity of salt when cooking. Whereas a study in China among general population found that almost all of the urban and rural population use low quantity of salt in cooking.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, control of salt intake is considered as a crucial element for a healthy and highly-qualified life [4,11,12]. It is believed that consuming high-fiber diets combined with reduced salt intake can play a critical role in prevention of hypertension and its fatal cardiovascular complications, as well as decreasing medical costs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%